Major applications and limitations of blood group genotyping in China. (15th February 2018) - Ji, Y. L.
Abstract : Molecular immunohematological techniques have been well applied in the transfusion medicine. Here, we review the major applications for blood group genotyping in China. Its application mainly focuses on the typing of blood group antigens in complex cases, such as ABO subgroups, D variants or the Asian specific and common antigens typing (such as the antigens expressed by the MNS hybrid glycophorins), also because of lacking of the corresponding commercial antibodies. The comprehensive antigens profile in some specific samples could be obtained using medium‐ or high‐throughput genotyping platforms. Although, foetal RHD genotyping in D– pregnant women in Europe is highly relevant to avoid unnecessary antenatal RhIg, it is of comparatively less importance in the Chinese D– pregnant women because of the low probability (3–4%) to have a D– baby. In contrast, the application of routine molecular testing for the 'Asia type' DEL, which having a frequency up to 30% in East Asian people serologically typed as D‐negative, is more necessary to avoid unnecessary administration of antenatal RhIg, because there is increasing evidence that individuals carrying the 'Asia type' DEL allele (c.1227G>A, p.Lys409Lys) do not produce alloanti‐D after exposure to D+ red blood cells. The molecular methods to detect the RHD*1227A are more accurate and applicable for routine testing of 'Asia type' DEL.